STRATEGI PEMBELAJARAN GURU PENDIDIKAN AGAMA ISLAM BAGI SISWA TUNARUNGU DI SLB NEGERI KANDANGAN: Strategi Guru PAI, Pembelajaran, Tunarungu - Fahrinawati; Rina Wahyuni; Sulaiman Jazuli (IAI DARUL ULUM KANDANGAN, 2024)
This research aims to find out the strategies of Islamic Religious Education teachers in learning for deaf students at the SLB Negeri Kandangan. This research is field research, with a qualitative descriptive. The subjects in this research were three Islamic religious education teachers who taught at the SDLB, SMPLB and SMALB levels. The object of this research is the strategy of Islamic Religious Education teachers in learning for deaf students at SLB Negeri Kandangan. The results of this research are the strategies of Islamic Religious Education Teachers in learning for deaf students at SLB Negeri Kandangan, namely deductive, expository, classical, behavior modification and group strategies.